Aplicação do método de fronteira imersa no estudo de escoamentos no fundo de poço, considerando brocas simplificadas. - Puelles, Sammy Cristopher Paredes (2019)
The present work deals with problems present in drilling processes, specifically in the bottom hole region. The drilling mud is pumped through the drilling column and ejected through the drill nozzles, the jets impact the bottom hole surface helping the dispersion of the particulate material result of curt, finally the flow continues its trajectory through the annular part. To represent this process, a simplified system composed by the well and drilling column was used, considering a Newtonian, incompressible fluid and without particles. The wellcolumn system was considered rigid and with no section change, any external force that could interact with the system was excluded. As a study tool we used a parallelized numerical code based on the solution of Navier-Stokes equations with second order spatial and temporal approximation, discretization using the finite volume method and large eddy simulation methodology for the treatment of the turbulence phenomenon. The immersed boundary method was used to represent the well-column system by means of a force field. Three simplified drill bits were proposed, two of PDC type and one of Triconic type. The results were satisfactory, since the fluid dynamics variables were proportionally influenced with the rotation of the drilling column, the flow path and the type of drill bit. Higher turbulent intensity was found between the drill and the bottom hole surface as a consequence of the jet action, the geometry and drill bits rotation. The impact force, which is a fundamental parameter in the drilling process, is highly dependent on the speed of rotation and the distance between the nozzle and the bottom hole. Another important contribution of the present work is associated with the potential of the numerical tool, in development, to deal with complex engineering problems.